Pengaruh Minat Belajar dan Kedisiplinan Siswa terhadap Prestasi Belajar Ilmu Pengetahuan Alam - Sri Kusmiati (Jurnal Arjuna : Publikasi Ilmu Pendidikan, Bahasa dan Matematika, 2024)
The aim of this research is to determine: (1) The influence of students' learning interest and discipline together on the natural sciences learning achievement of State MTs students in West Jakarta. (2) The influence of interest in learning on the natural science learning achievement of State MTs students in West Jakarta. (3) The influence of student discipline on the Natural Sciences learning achievement of State MTs Students in West Jakarta. The research was conducted at MTs in West Jakarta, especially MTs Negeri 36 Jakarta and MTs Negeri 11 Jakarta. The population in this study was 711 students so the sample used was 71 students. The method used is a survey method with multiple regression test data analysis. The results of hypothesis testing show (1) There is a significant influence on students' learning interest and discipline together on the natural science learning achievement of State MTs students in Jakarta. This is proven by the sig value. = 0.000 < 0.05 and calculated F = 11.320. (2) There is a significant influence of interest in learning on the natural science learning achievement of State MTs students in Jakarta. This is proven by the sig value. = 0.002 < 0.05 and t = 3.217. (3) There is a significant influence of student discipline on the natural science learning achievement of State MTs students in Jakarta. This is proven by the sig value. = 0.003 < 0.05 and t = 3.116.